Effects of Rhodiola rosea and aspirin on behaviour and some biochemical parameters in old mice - Derkachov, Vitalii; Berezovskyi, Vladyslav (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2024)
Abstract. This study investigates the effects of aqueous Rhodiola rosea extract and low-dose and high-dose aspirin on behaviour and biochemical parameters in aged C57BL/6J mice. Both substances are widely recognized for their therapeutic properties and potential geroprotective effects in simpler organisms such as yeast and Drosophila. Aspirin, or acetylsalicylic acid, is a medication used for the treatment of pain and fever and also possesses anti-inflammatory and antipyretic properties. It is found to prolong lifespan of model organisms if taken throughout life but not in the old age. R. rosea is considered a geroprotector with rejuvenating properties. It contains a variety of compounds that may act as anti-inflammatory or anti-cancer agents. Additionally, evidence suggests that R. rosea extracts improve quality of life in the elderly and extend lifespan. Mice aged 17 months (comparable to approximately 80 human years) were administered R. rosea extract or aspirin (5 mg/kg and 25 mg/kg body mass daily) for two months. Behavioural assessment using the open field test revealed no significant differences between the groups, although trends suggested increased anxiety-like behaviour in mice receiving 25 mg aspirin. Biochemical analysis showed no statistically significant changes in lipid peroxidation in the brain or liver enzyme activities (alanine aminotransferase, ALT, and aspartate aminotransferase, AST), although a trend toward elevated ALT activity with aspirin supplementation was observed, indicating potential liver stress. These findings highlight the complexity of assessing geroprotective interventions in aged organisms and suggest that both R. rosea extract and aspirin, at the tested doses, may have limited efficacy in improving healthspan in older mice. Further studies with larger cohorts and additional biomarkers are needed to explore these preliminary findings.